2017
DOI: 10.1093/bioinformatics/btx125
|View full text |Cite
|
Sign up to set email alerts
|

AQUA-DUCT: a ligands tracking tool

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…Therefore, we decided to use water molecules as a kind of non-specific probe and performed detailed computational simulations to investigate possible mechanisms regulating solvent access to the active site to identify changes introduced by specific mutations. Molecular Dynamics simulations (MD) of DAAOs in water were done using AMBER package [ 48 ], the tunnel network analysis was performed using CAVER [ 49 ], and a water tracking study was done using AQUA-DUCT software [ 50 ]. The mentioned procedure was applied for pkDAAO, hDAAO and selected hDAAO mutants.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we decided to use water molecules as a kind of non-specific probe and performed detailed computational simulations to investigate possible mechanisms regulating solvent access to the active site to identify changes introduced by specific mutations. Molecular Dynamics simulations (MD) of DAAOs in water were done using AMBER package [ 48 ], the tunnel network analysis was performed using CAVER [ 49 ], and a water tracking study was done using AQUA-DUCT software [ 50 ]. The mentioned procedure was applied for pkDAAO, hDAAO and selected hDAAO mutants.…”
Section: Resultsmentioning
confidence: 99%
“…Their tool consists of a set of linked views, enabling the exploration and filtering of trajectories, based on user‐defined criteria and thresholds. It integrates the clustering of trajectories, proposed by Góra et al [MMG*17]. However, our case studies revealed that experts sometimes need to investigate small‐scale interations between a single water molecule and a ligand in more detail.…”
Section: Related Workmentioning
confidence: 97%
“…AQUA-DUCT [62,63] aims to provide detailed insights into the process of how a given type of molecules, such as water, ions, gasses, or any other kind of ligand, penetrates through the selected region of a protein ( Figure 3A). As a minimal input, the user has to provide an MD trajectory and a configuration file describing two important regions for the analysis and defining the traced ligand.…”
Section: Analyses Of Ligand Transportmentioning
confidence: 99%
“…Additionally, a statistical analysis is performed for all clusters, enumerating the number of the evaluated molecules, paths, inlets, and clusters, and several more specific statistics, including the lengths of the paths or the durations of the transport events. To illustrate the computational demands, the AQUA-DUCT analysis of 100 ns long MD simulations of murine epoxide hydrolase (4992 protein atoms) surrounded by 8488 water molecules requires 8-12 h to execute on a powerful workstation (Intel Core i7 CPU @ 3.50GHz machine, 64 GB RAM) [62]. For visualization purposes, a PyMOL [82] script or session can be generated according to user specifications.…”
Section: Analyses Of Ligand Transportmentioning
confidence: 99%